2005
DOI: 10.1021/es047956k
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Carbon Tetrachloride by Thiol Reductants in the Presence of Quinone Compounds

Abstract: Quinones are present in trace amounts in natural organic matter. The addition of thiol compounds to quinones produces reactive electron-transfer species that may be important for the transformation of chlorinated hydrocarbons under sulfate-reducing conditions. This study systematically investigated the transformation of carbon tetrachloride (CCl4) in homogeneous aqueous solutions containing quinones as electron-transfer mediators and thiol compounds as bulk reductants. The thiol compounds, including sodium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…Electron shuttle-mediated contaminant transformation has been demonstrated for the BTEX compounds (11,39), methyl tert butyl ether (11,12), carbon tetrachloride (9), and metals such as uranium (12,15,25,26,30). The role of electron shuttling in environmental reactions was reviewed by Hernandez and Newman (24).…”
mentioning
confidence: 99%
“…Electron shuttle-mediated contaminant transformation has been demonstrated for the BTEX compounds (11,39), methyl tert butyl ether (11,12), carbon tetrachloride (9), and metals such as uranium (12,15,25,26,30). The role of electron shuttling in environmental reactions was reviewed by Hernandez and Newman (24).…”
mentioning
confidence: 99%
“…To our knowledge, this is the first demonstration of the utilization of thermodynamic properties of the electron donor to selectively stimulate specific respiratory processes. Although earlier studies have ð5860 mequiv:=6133 mequiv:ÞÂ100 ¼ 95:6% electron balance used AH 2 DS as a reductant for transformation of contaminants, such as hexahydro-1,3,5-trinitro-1,3,5-triazine (Kwon and Finneran, 2006) and carbon tetrachloride (Doong and Chiang, 2005), data presented here indicate that microbial AH 2 DS oxidation can support bioremediative processes as well.…”
Section: Discussionmentioning
confidence: 57%
“…Our previous study showed that cysteine in the concentration range 0.5-2 mM is an effective mediator to transfer electrons between Geobacter sulfurreducens and ferrihydrite [27]. High concentrations of cysteine and AQDS have also been used as reductants for the abiotic dechlorination of CT under anoxic conditions [1,17,18]. These results clearly show that both AQDS and cysteine can be used in chemical and biological reactions for degradation of priority pollutants under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 78%
“…The headspace analytical technique was used for the determination of chlorinated hydrocarbons [2,3,17]. The concentrations of CT and byproducts in the headspace of the test bottles were monitored by withdrawing 50 L of gas from the headspace and then injecting into a gas chromatograph (GC, Perkin-Elmer, Autosystem) equipped with an electron capture detector (ECD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation